2018
DOI: 10.3390/molecules23010107
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecule-Functionalized Smart Polydiacetylene for Biomedical and Environmental Sensing

Abstract: Polydiacetylene (PDA) has attracted interest for use as a sensing platform in biomedical, environmental, and chemical engineering applications owing to its capacity for colorimetric and fluorescent transition in response to external stimuli. Many researchers have attempted to develop a tailor-made PDA sensor via conjugation of chemical or biological substances to PDA. Here, we review smart bio-conjugates of PDA with various biomolecules such as carbohydrates, lipids, nucleic acids, and proteins. In addition, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 96 publications
0
18
0
Order By: Relevance
“…Printed inks were irradiated with UV‐C light (254 nm) for 1‐4‐addition‐polymerization to yield covalent connectivity between adjacent diacetylenes, forming PDA with an ene‐yne alternating backbone structure. [ 24 ] The blue color of the printed inks, which was developed during the polymerization, was expected to have chromatic change to red upon the immunocapture of E. coli and its antigens. For this study, we utilized two PDA bioinks without and with the antibody conjugation, which were printed in patterns “C” and “E,” representing “Control” and “ E. coli targeting”, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Printed inks were irradiated with UV‐C light (254 nm) for 1‐4‐addition‐polymerization to yield covalent connectivity between adjacent diacetylenes, forming PDA with an ene‐yne alternating backbone structure. [ 24 ] The blue color of the printed inks, which was developed during the polymerization, was expected to have chromatic change to red upon the immunocapture of E. coli and its antigens. For this study, we utilized two PDA bioinks without and with the antibody conjugation, which were printed in patterns “C” and “E,” representing “Control” and “ E. coli targeting”, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, polydiacetylene (PDA) liposomes have been extensively investigated due to the rapid color change (blue‐to‐red) and fluorescence generation induced by the conformal change of the backbone as a response to environmental perturbations such as heat, temperature, and mechanical pressure. [ 22,23 ] To be used in sensors to target specific chemicals or microorganisms, [ 24 ] PDA can be fabricated in the format of nano‐ or microliposomes and functionalized with various macromolecules such as carbohydrates, [ 25 ] lipids, [ 26 ] peptides, [ 27 ] and antibodies. [ 28,29 ] However, immobilization of colorimetric sensors on the inside of packaging material or in sachet limits the sensing efficacy to pathogens present on food surfaces and reduces the detection of pathogenic microorganisms that grow in microscopic cavities or inside food.…”
Section: Introductionmentioning
confidence: 99%
“…For this synthesis, 5% ganglioside lipid was used as a function that be used as a site of action against the targeted site, Using a higher concentration it was found that it will inhibits polymerization of the diacetylene and stops its formation and as are selt no diagnostic ability for this polymer. 8 The addition of bacterial supernatants caused a colorimetric transition in TDER/PCDA vesicles, even in diluted concentrations, which indicate that a certain chemical interactions occur between the vesicles and the released bacterial toxin compounds. This study was important for food packing and Food born bacteriatypes.…”
Section: Polydiacetylenes As Bio Sensormentioning
confidence: 96%
“…Sodium polystyrene sulfonate (KayexalateVR , SPS) is the first known type of Polymer which is the first synthetic polymers to be widely used as a clinical sequestrate, its strecture is shown in scheme.4 the salt of a polymeric acid, SPS is able to reversibly bind a verity of captions, including potassium.Since potassium is the most popular ion in the colon region as part of intestinal gastric tracts, and is reversibly absorbed in this lower part GI tract, So polymeric agent with capability to such potassium this ion will provide an effective means to reduce serum potassium( Elevated serum potassium)and as a result it will releave kidney diseases . (hyperkalemia) is a disease with incorporated with patient suffering from CKD or cardiovascular conditions which will result in arrhythmia and finally to sudden death [8]. SPS was approved by the FDA for its use on the treatment of hyperkalemia in 1958 SPS which can be synthesized by the polymerization of styrene in in presence of cross linking agent such as divinylbenzene as shown below: Scheme 4 hows the synthetic steps of polystyrene sulfonate Sevelamer hydrochloride (Renage lVR) was the first polymeric phosphate control and removal of excess phosphate is of highly beneficial to patients with chronic kidney disease CKD where dialysis is unable to maintain safe phosphorus levels.…”
Section: Polymers As Drugsmentioning
confidence: 99%
“…However, its potential use in sensing application was rst explored by Charych et al [6]. The PDA vesicles have received tremendous attention in the eld of chemical and biological sciences as a colorimetric sensor due to their capacity to change the color when exposed to various external stimuli such as light, heat, mechanical stress, solvents and binding of speci c chemical or biological agents [7][8][9]. The blue phase of the vesicles shows maximum absorption at 640 nm and red phase, at 550 nm when exposed to external stimuli, which can be directly observed by the naked eyes [10][11][12].…”
Section: Introductionmentioning
confidence: 99%